The Jewish–Arab Conflict and the Disintegration of the Ancient Jewish Community in the Village of Peqi'in. Issue 4 (1st October 2016) - Ben-Dror, Elad
Abstract: The fate of the last community of Arabized Jews in Palestine, in the Galilee village of Peqi'in is surveyed. Peqi'in (al-Baqi'a in Arabic) is still known as the "Village of the Four Religions, " because of its unique mix of Jews, Christians, Muslims, and Druze, who lived together for centuries in good neighborly relations. Although the Arab-Jewish conflict might not have seemed relevant to the Peqi'in Jews, who had lived there for centuries, they were ultimately pushed out of the village. This pioneering study describes how the Peqi'in Jews, who had became a symbol for the Zionist enterprise, were forced from their home, although senior Zionist leaders strove to protect them and even made them a test of the alliance between the Zionists and the Druze. The sequence of events is recounted, from the start of the Mandate through the stillborn attempt to return the Peqi'in Jews to the village after the establishment of Israel.